2021
DOI: 10.1111/ijd.15330
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin in vitiligo: an update with recent review of the literature

Abstract: Patients with vitiligo often seek medical attention, as it diminishes their quality of life resulting in significant morbidity. Several topical and systemic therapies are in vogue targeting the immunological aspect of this disease, but results are often unsatisfactory, and complete cure remains elusive. Recently, simvastatin, a 3‐hydroxy‐3‐methylyglutaryl‐coenzyme A (HMG‐CoA) reductase inhibitor, is being evaluated for vitiligo management because of its multimodal action, easy availability, and low cost. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…This discrepancy might be due to a low statin dose as a higher dose of systemic statins can cause cutaneous adverse reactions [ 41 ]. Exploring topical statin application offers a promising alternative, allowing for potentially higher local concentrations with minimal adverse effects [ 89 ]. A double-blind placebo-controlled RCT demonstrated that adding topical atorvastatin 5% cream to betamethasone 1% ointment was more effective in treating chronic HE ( n = 44) after 10 days compared to betamethasone ointment plus a vehicle cream ( n = 44), as evidenced by significantly greater reductions in HE severity and itching and improvements in quality of life [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be due to a low statin dose as a higher dose of systemic statins can cause cutaneous adverse reactions [ 41 ]. Exploring topical statin application offers a promising alternative, allowing for potentially higher local concentrations with minimal adverse effects [ 89 ]. A double-blind placebo-controlled RCT demonstrated that adding topical atorvastatin 5% cream to betamethasone 1% ointment was more effective in treating chronic HE ( n = 44) after 10 days compared to betamethasone ointment plus a vehicle cream ( n = 44), as evidenced by significantly greater reductions in HE severity and itching and improvements in quality of life [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, data from vitiligo patients in Dell 'Anna et al (2007'Anna et al ( , 2010, in vitro mechanistic study (Hauff et al, 2009), and animal model (Han et al, 2007) indicated that higher demand for cholesterol synthesis (e.g., for cell grow or LDLcholesterol increases) is detrimental to mitochondrial cardiolipin content. This rationale is supported by data who statin mitigating the vitiligo spreading (Hasan et al, 2021). Statins have a lower effect on LDL-cholesterol via HMG-CoA reductase inhibition.…”
Section: A Possible Link Between Vitiligo Onset and Progression With ...mentioning
confidence: 91%
“…This may be because higher doses are required for its effectiveness. It is anticipated that the topical therapy can provide a sufficiently high local concentration, for which a topical simvastatin salt trial (EVRAAS trial) is underway [ 46 , 47 ]. Aspirin has antioxidant activity and has good preventive and therapeutic effects against many oxidative stress-related diseases.…”
Section: Oxidative Stress and Vitiligomentioning
confidence: 99%